2017
DOI: 10.11648/j.sjac.20170503.11
|View full text |Cite
|
Sign up to set email alerts
|

Salting-out Assisted Liquid-Liquid Extraction for the Determination of Multiresidue Pesticides in Alcoholic Beverages by High Performance Liquid Chromatography

Abstract: Abstract:A salting-out assisted liquid-liquid extraction (SALLE) method followed by high-performance liquid chromatography with ultraviolet-visible detector (HPLC-UV/Vis) has been proposed for determination of five multiclass pesticides residues including, atrazine, ametryn, terbutryn, carbaryl and chlorothalonil from various alcoholic beverages: beer, wine and Ethiopian honey wine (Tej). Experimental parameters influencing the extraction efficiency of the method such as the type and concentration of salt, vol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 38 publications
(75 reference statements)
0
13
0
Order By: Relevance
“…For efficient extraction of ionizable and relatively polar compounds, pH of the sample solution plays a decisive role. The sample solution pH should be lower than the pK a of the analytes to obtain the target analytes in their unionized forms so that they have a higher tendency to partition into the organic phase [43]. The effect of varying pH values of the sample solution on the extraction efficiency was studied in the range of 3.0–8.0.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For efficient extraction of ionizable and relatively polar compounds, pH of the sample solution plays a decisive role. The sample solution pH should be lower than the pK a of the analytes to obtain the target analytes in their unionized forms so that they have a higher tendency to partition into the organic phase [43]. The effect of varying pH values of the sample solution on the extraction efficiency was studied in the range of 3.0–8.0.…”
Section: Resultsmentioning
confidence: 99%
“…At acidic conditions they are in cationic form, which is important for their retention during the extraction. At basic conditions, the anionic species of both acidic and piperazinylic quinolones are less retained in comparison to cationic, zwitterionic and neutral species [43, 44].…”
Section: Resultsmentioning
confidence: 99%
“…Salting out Liquid-Liquid extraction method followed by high performance liquid chromatography with ultraviolet-visible detector has been reported for the analysis of atrazine, ametryn, terbutryn, carbaryl and chlorothalonil in beer, wine and Ethiopian honey wine [3]. Under the optimum experimental conditions, matrix-matched calibration curves were constructed using beer sample as the representative matrix and good linearity over wide concentration ranges were obtained with R 2 of 0.997.…”
Section: Liquid -Liquid Extractionmentioning
confidence: 99%
“…A literature survey revealed that a variety of sample preparation techniques based on liquid and solid phases within the years 2006−2021 had been published for the cleanup and extraction of pesticide residues in malt-based beverages, including solid-phase extraction (SPE), 14,15 solvent extraction (SE), 6,14,16,17 Quick, Easy, Cheap, Effective, Rugged, and Safe (QuEChERS) method, 7,13 liquid−liquid extraction (LLE), 18 and salting-out assisted LLE (SALLE) method. 19 These sample preparation methods have been coupled with gas chromatography−mass spectrometry selective-ion monitoring (GC−MS/SIM), 14 LC−MS/MS, 13,15,16,18,20 gas chromatography−electron capture detection (GC−ECD), 17 gas chromatography−mass spectrometry (GC−MS), 18 gas chromatography with tandem mass spectrometry (GC−MS/MS), 7 and liquid chromatography with ultraviolet/visible. 19 The aim of this work was to develop a green analytical procedure for the analysis of multiclass pesticide residues in nonalcoholic malt beverages.…”
Section: ■ Introductionmentioning
confidence: 99%
“…19 These sample preparation methods have been coupled with gas chromatography−mass spectrometry selective-ion monitoring (GC−MS/SIM), 14 LC−MS/MS, 13,15,16,18,20 gas chromatography−electron capture detection (GC−ECD), 17 gas chromatography−mass spectrometry (GC−MS), 18 gas chromatography with tandem mass spectrometry (GC−MS/MS), 7 and liquid chromatography with ultraviolet/visible. 19 The aim of this work was to develop a green analytical procedure for the analysis of multiclass pesticide residues in nonalcoholic malt beverages. For this, a green alternative micro-solid phase extraction based on natural materials was developed.…”
Section: ■ Introductionmentioning
confidence: 99%